Unveiling the complexities of mild stroke: An interpretative phenomenological analysis of the mild stroke experience. (9th October 2019) - Hodson, Tenelle; Gustafsson, Louise; Cornwell, Petrea
Abstract : Introduction: Limited research has been conducted from a longitudinal and qualitative perspective on the experience of life after mild stroke. This restricts the knowledge held in this area. This study aimed to answer the question: How do people with mild stroke understand their experiences in the first 6 months after hospital discharge? Methods: Interpretative Phenomenological Analysis, involving five Australians with mild stroke, interviewed at 1‐, 3‐ and 6 months post‐hospital discharge. Results: Two themes emerged about the transitional journeys post‐mild stroke: (i) Understanding and representation of stroke and (ii) Underlying relationship dynamics revealed . The first theme had two subthemes: (i) Society defines the stroke experience, and (ii) The past determines the present. The first of these reflected the impact that societal perceptions of 'stroke' had on participants' views of their mild stroke, including feelings of being 'lucky' even when experiencing hidden difficulties that were viewed as liveable repercussions. The second explores how previous health conditions acted as a mediator for participants' experiences of the mild stroke and how personal attributes assisted adaption to post‐mild stroke changes. The final theme highlights how participants' relationships were either strengthened or weakened after the mild stroke, dependent on previous relationship dynamics. Conclusion: Current societal perceptions of stroke are centred on 'observable' symptoms; however, more subtle symptoms common in the mild stroke population remain widely unknown by the general public impacting post‐mild stroke experiences. Previous health conditions and personal attributes have an impact on how people react to their mild stroke and help to explain the individualist nature of mild stroke outcomes. Relationship dynamics prior to mild stroke can impact on post‐mild stroke family functioning, and should be screened for, and supported by health professionals. All of these factors emphasise the need for a patient‐centred and multidisciplinary approach when determining interventions.